2019
DOI: 10.1109/access.2019.2907120
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Management System With Optimum Reserve Power Procurement Function for Microgrid Resilience Improvement

Abstract: Power system decentralization has been an emerging topic for the past decade in an effort to improve power quality and environment protection via the increased integration of renewable energy sources. Toward these objectives, decentralized microgrids have been proposed and thoroughly investigated in terms of technical capabilities and economic performance. In fact, the planning and actual operation of small-scale, decentralized microgrids have started in countries, such as Canada, Japan, USA, U.K., and other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The CBESS is decided to charge surplus power from the MG system and discharge during intervals having shortage power. Constraints (26) and (27) show the bounds for charging/ discharging amount at an interval of time. These constraints also ensure that the charging mode is possible when the MG has surplus power, while the discharging mode is possible when the MG has shortage power.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The CBESS is decided to charge surplus power from the MG system and discharge during intervals having shortage power. Constraints (26) and (27) show the bounds for charging/ discharging amount at an interval of time. These constraints also ensure that the charging mode is possible when the MG has surplus power, while the discharging mode is possible when the MG has shortage power.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The information of the CDG unit, BESS, and CBESS are tabulated in Table 1. The operation bounds of BESS and CBESS were chosen as [0%, 100%], same as [27]. The detailed numerical results are shown in the following sections for both grid-connected and islanded modes.…”
Section: Input Datamentioning
confidence: 99%
“…Furthermore, to build transmission lines and distribution lines, as well as new communications infrastructure to serve the traditional power systems, is becoming more and more challenging due to, for instance, growing pressures over environmental licensing, funding allocation, etc. It has been suggested that the centralized paradigm of energy delivery is reaching its technical boundaries and no longer seems to constitute the most effective approach for granting continuous and reliable power supply to customers located at the edge of the grid, especially in countries with a high percentage of non-urban area installations [1]. The above trends have led to increasing interest in installing small scale generation closer to the consumption nodes -Distributed Energy Resources (DER).…”
Section: Introductionmentioning
confidence: 99%
“…Energy storages in MG domain require great attention on various aspects, such as type (material and size) and cost of energy storage devices, efficient energy management strategies, power conditioning sub-systems, chargingdischarging cycle, power conversion mechanism, and control for stable operation, protection, reliability, and environment friendly [38][39][40]. By virtue, MG should be capable of operating in both grid-connected and isolated mode, where MG isolated mode of operation is challenging because of a power imbalance between generations and load that result in voltage and frequency instability [38,[41][42].…”
Section: Introductionmentioning
confidence: 99%